Thermal Comfort Determines User Subjectivity in Lamongan Grand Mosque - Agustapraja, Hammam Rofiqi; Wahab, Izudinshah bin Abd; Digdaya, Alfin Bagas (Jurnal Teknik, 2025)
Mosque is a place of worship, which requires comfort to enhance the quality of worship, thermal comfort being one of the considerations in the prayer space of the mosque. This study aims to analyze the level of thermal comfort and thermal preferences of users in the interior space of the Grand Mosque of Lamongan. The method used is quantitative, collecting data through surveys at the Grand Mosque of Lamongan. Some of the data collected include personal data (clothing and activities) and measurements of environmental parameters; air temperature, air humidity, and wind speed. At the same time, users were asked to fill out a questionnaire asking about their perceived level of comfort at that time. The results of the study show that the interior space of the mosque has an average temperature ranging from 28.4 ºC to 29.08 ºC, while the survey questionnaire results indicate that 89.1% of respondents can accept the existing thermal conditions. This may be due to the fact that the temperature inside the mosque is much lower compared to the outdoor temperature.